Ciri-ciri pekerja bertingkah laku hijau: satu tinjauan awal - Mukhiffun Mukapit,; Siti Fardaniah Abdul Aziz,; Mohd Nasir Selamat,; Noordeyana Tambi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Employee green behavior is a major component of the organization's green strategic planning. Nonetheless, the existence of symbolic behavior in its implementation has made the determination of employee green behavior characteristic vague. Therefore, a literature review was done to determine the characteristics of employee green behavior. These characteristics are explained using various theories and models as well as findings from previous research on the evolution of employee's green behavior characteristics. Previous studies demonstrate that the characteristics of employee green behavior comprise of one or two main dimensions. However, the characteristics of employee green behavior on the basis of organization's strategic green planning are still unclear because of the existence of symbolic behavior. Hence, this article proposes the characteristics of the employee green behaviour on the basis of organizational green strategic planning.